Hippocampal expression of murine TNFα results in attenuation of amyloid deposition in vivo - Paramita Chakrabarty; Amanda Herring; Carolina Ceballos‐Diaz; Pritam Das; Todd E. Golde (2011)
Fibrillar amyloid β (fAβ) peptide is the major component of Aβ plaques in the brains of Alzheimer's disease (AD) patients. Inflammatory mediators have previously been proposed to be drivers of Aβ pathology in AD patients by increasing amyloidogenic processing of APP and promoting Aβ accumulation, but recent data have shown that expression of various inflammatory cytokines attenuates Aβ pathology in mouse models. In an effort to further study the role of different inflammatory cytokines on Aβ pathology in vivo, we explored the effect of murine Tumor Necrosis Factor α (mTNFα) in regulating Aβ accumulation. Recombinant adeno-associated virus serotype 1 (AAV2/1) mediated expression of mTNFα in the hippocampus of 4 month old APP transgenic TgCRND8 mice resulted in significant reduction in hippocampal Aβ burden. No changes in APP levels or APP processing were observed in either mTNFα expressing APP transgenic mice or in non-transgenic littermates. Analysis of Aβ plaque burden in mTNFα expressing mice showed that even after substantial reduction compared to EGFP expressing age-matched controls, the Aβ plaque burden levels of the former do not decrease to the levels of 4 month old unmanipulated mice. Taken together, our data suggests that proinflammatory cytokine expression induced robust glial activation can attenuate plaque deposition. Whether such an enhanced microglial response actually clears preexisting deposits without causing bystander neurotoxicity remains an open question.